Law and political power - Chambliss, William (1972)
This paper addresses the conception of law and its functions in society. In this order of ideas, the authors begin by analyzing the conception of law as a "right of action", "set of processes" and its function of social engineering. On the other hand, the authors analyze the law, and its values, from the study of the doctrine of natural law, positivism and legal realism. Throughout the article, the doctrinal positions developed by various jurists with respect to the theory of law are appreciated: Von Savigny, Maine, Bohannan, Fuller, Hobbes, Bentham, Austin, Wendell, among others. And finally, the authors reflect on political theory and values in law with respect to the State.